Orienteering Running: Setting Up Courses and Methods for Team Training – 1991 Republication: A Historical and Methodological Retrieval - Miranda, André Luis Novaes de (2021)
Introduction: The orienteering race is a race through the field that takes place against the clock in a defined route, marked by checkpoints, which the participant must pass. Objective: The article aimed to present methods of physical and technical preparation, as well as to present route assembly techniques. Methods: Books, articles and technical experts in the modality were consulted. Results: The following topics were presented: physical effort; physical skills of the advisor; training methods; technical training; and course assembly techniques Conclusion: It was expected to have contributed to taking the sport of orienteering running to those who do not know it yet, as well as consolidating the knowledge of practitioners and coaches.